2000
DOI: 10.1128/iai.68.3.1034-1039.2000
|View full text |Cite
|
Sign up to set email alerts
|

Shigella flexneri 2a Strain CVD 1207, with Specific Deletions in virG , sen , set , and guaBA , Is Highly Attenuated in Humans

Abstract: A phase 1 clinical trial was conducted among 35 healthy adult volunteers to evaluate the safety, immunogenicity, and shedding of different doses of CVD 1207, a live attenuated Shigella flexneri 2a vaccine candidate with specific deletion mutations in virG, sen, set, and guaBA. CVD 1207 retains the ability to invade epithelial cells but cannot effectively spread intercellularly after invasion (⌬virG), does not produce enterotoxin (⌬sen and ⌬set), and has limited proliferation in vivo (⌬guaBA). In a consecutive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
64
1

Year Published

2000
2000
2010
2010

Publication Types

Select...
3
2
2

Relationship

2
5

Authors

Journals

citations
Cited by 84 publications
(65 citation statements)
references
References 40 publications
(34 reference statements)
0
64
1
Order By: Relevance
“…When volunteers ingested escalating single doses of up to 10 10 CFU of CVD 1207 (REF. 87), this live vaccine strain was remarkably well tolerated. No subjects manifested adverse reactions through the 10 8 CFU dosage level 87 , and even at 10 9 and 10 10 CFU only a few volunteers experienced mild diarrhoea 87 .…”
Section: Selection Of Attenuating Mutationsmentioning
confidence: 99%
See 2 more Smart Citations
“…When volunteers ingested escalating single doses of up to 10 10 CFU of CVD 1207 (REF. 87), this live vaccine strain was remarkably well tolerated. No subjects manifested adverse reactions through the 10 8 CFU dosage level 87 , and even at 10 9 and 10 10 CFU only a few volunteers experienced mild diarrhoea 87 .…”
Section: Selection Of Attenuating Mutationsmentioning
confidence: 99%
“…87), this live vaccine strain was remarkably well tolerated. No subjects manifested adverse reactions through the 10 8 CFU dosage level 87 , and even at 10 9 and 10 10 CFU only a few volunteers experienced mild diarrhoea 87 . The conclusion from the Phase I clinical trial of CVD 1207 was that the mutations definitively attenuated the 2457T parent strain, resulting in a vaccine that was well tolerated by North American volunteers at high dosage levels yet remained immunogenic.…”
Section: Selection Of Attenuating Mutationsmentioning
confidence: 99%
See 1 more Smart Citation
“…4B). Although the ⌬virG strain has been used as an attenuated live vaccine in several studies, including in clinical trials (14,21,(25)(26)(27), these findings suggested that bacteria with single mutation in the virG gene retain virulence in mice when inoculated with a large number of bacteria. Low dose (2 ϫ 10 7 CFU) infection of ⌬virG also caused significant body weight loss, to a maximum of 22.3 Ϯ 5.53% ( p Ͻ 0.05; n ϭ 10), compared with the saline-vaccinated mice.…”
Section: Experimental Morbidity Induced By the ⌬Ipab/inv Strain In Vivomentioning
confidence: 99%
“…These strains have been classified into two groups on the basis of the function of the mutated gene: 1) strains in which one or two genes in the metabolism have been inactivated, such as thyA, aroA, and aroD (15)(16)(17), and 2) strains harboring mutation of virG (icsA), a gene essential for cell-to-cell spreading, in addition to one of above gene mutations (18 -24). The ⌬virG strain has been widely used as an attenuated live vaccine strain or in combination with mutation in other gene(s) in several studies, including in clinical trials (14,21,(25)(26)(27). The vaccine strain, SC602, which has mutations in the virG gene and the aerobactin iuc locus, has proceeded to phase 2 trials in humans.…”
Section: High Vaccine Efficacy Against Shigellosis Of Recombinant Nonmentioning
confidence: 99%